2020
DOI: 10.3390/molecules25133053
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of ZeoliticWaste in Alkali-Activated Biomass Bottom Ash Blends

Abstract: This study aims to investigate the effects of ammonium-bearing zeolitic waste (FCC) on alkali-activated biomass bottom ash (BBA). FCC was obtained from the oil-cracking process in petroleum plants. In this study, two types of production waste were used: biomass bottom ash and ammonium-bearing zeolitic waste. These binary alkali-activated FCC/BBA blends were investigated using X-ray diffraction (XRD), Fourier transform infrared (FTIR) and scanning electron microscopy (SEM) methods. The compressive stren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Geopolymers are favored with respect to crystalline zeolite when Si:Al > 1.5. This limit has been empirically established [ 1 , 12 ] yet addition of SiO 2 [ 13 ] or SiO 2 and Al 2 O 3 -rich fillers/additives [ 14 , 15 ] helps to increase such Si:Al ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Geopolymers are favored with respect to crystalline zeolite when Si:Al > 1.5. This limit has been empirically established [ 1 , 12 ] yet addition of SiO 2 [ 13 ] or SiO 2 and Al 2 O 3 -rich fillers/additives [ 14 , 15 ] helps to increase such Si:Al ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption bands at 1098, 798, and 470 cm −1 are assigned to the asymmetric Si-O-Si stretch, the symmetric Si-O-Si stretch, and Si-O-Si deformation, respectively [14]. The bands at 875 and 1445 cm −1 are attributed to the presence of carbonate (CO3 2− ) vibrations [15]. The bands in the 2365 and 2338 cm −1 range are attributed to the stretching of adsorbed CO2 [16,17].…”
Section: Adsorbent Characterizationmentioning
confidence: 98%
“…It is reported that biomass ash contains high amount of heavy metals, such as arsenic (As), cadmium (Cd), zinc (Zn), lead (Pb), chromium (Cr), copper (Cu), etc. [27][28][29]. Therefore, under the pressure to minimise environmental loads, the disposal of some hazardous biomass ash has been listed and highlighted in the agenda.…”
Section: Introductionmentioning
confidence: 99%